Immune Cell Confrontation in the Papillary Thyroid Carcinoma Microenvironment - Xie, Zhenyu; Li, Xin; He, Yuzhen; Wu, Song; Wang, Shiyue; Sun, Jianjian; He, Yuchen; Lun, Yu; Zhang, Jian (Frontiers in Endocrinology, 2020)
Background: Papillary thyroid carcinoma (PTC) is classified as an inflammation-driven cancer. A systematic understanding of immune cell infiltration in PTC is essential for subsequent immune research and new diagnostic and therapeutic strategies. Methods: Three different algorithms, single-sample gene set enrichment analysis (ssGSEA), immune cell marker and CIBERSORT, were used to evaluate the immune cell infiltration levels (abundance and proportion) in 10 data sets (The Cancer Genome Atlas [TCGA], GSE3467, GSE3678, GSE5364, GSE27155, GSE33630, GSE50901, GSE53157, GSE58545, and GSE60542; a total of 799 PTC and 194 normal thyroid samples). Consensus unsupervised clustering divided PTC patients into low-immunity and high-immunity groups. Weighted gene coexpression network analysis (WGCNA) and gene set enrichment analysis (GSEA) were used to analyze the potential mechanisms that cause differences in the immune response. Results: Compared with normal tissues, PTC tissues had a higher overall immune level, and the M2 macrophages, Tregs, monocytes, neutrophils, dendritic cells (DCs), mast cells (MCs), and M0 macrophages had higher abundances and proportions in PTC tissues. Compared with early PTC, advanced PTC had higher immune infiltration, and M2 macrophages, Tregs, monocytes, neutrophils, DCs, MCs, and M0 macrophages had higher abundances and proportions in advanced PTC. Compared to the low-immunity group patients, the high-immunity group patients presented with a more advanced stage, a larger tumor size, greater lymph node metastasis, higher tall-cell PTC, lower follicular PTC proportions, more BRAF mutations and fewer RAS mutations. Epstein-Barr virus (EBV) infection was the most significantly enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway for key module genes. Conclusions: In human PTC, M2 macrophages, Tregs, monocytes, neutrophils, DCs, MCs, and M0 macrophages played a tumor-promoting role, while M1 macrophages, CD8+ T cells, B cells, NK cells, and T follicular helper (TFH) cells (including eosinophils, γδ T cells, and Th17 cells, with weak supporting evidence) played an antitumor role. During the occurrence and development of PTC, the overall immune level was increased, and the abundance and proportion of tumor-promoting immune cells were significantly increased, indicating that immune escape had aggravated. Finally, we speculate that EBV may play an important role in changing the immune microenvironment of PTC tumors.